PENYULUHAN TENTANG PERAWATAN PAYUDARA PADA IBU NIFAS DI DESA NYALABU LAOK - Atiyetul Jesilah; Qurratul A’yun M.Kes (Bajang Institute, 2024)
Breast care education in Nyalabu Laok Village aims to increase public awareness about the importance of breast care when breastfeeding. This is because the breast is the only producer of breast milk, which is the staple food for newborn babies, so it must be done as early as possible. Exclusive breastfeeding and the correct breastfeeding process are reliable means for building quality human resources. Apart from that, in the correct breastfeeding process, babies will get good physical, emotional and spiritual development in their lives.